Amnion-Derived Teno-Inductive Secretomes: A Novel Approach to Foster Tendon Differentiation and Regeneration in an Ovine Model - Citeroni, Maria Rita; Mauro, Annunziata; Ciardulli, Maria Camilla; Di Mattia, Miriam; El Khatib, Mohammad; Russo, Valentina; Turriani, Maura; Santer, Michael; Della Porta, Giovanna; Maffulli, Nicola; Forsyth, Nicholas R.; Barboni, Barbara (Frontiers in Bioengineering and Biotechnology, 2021)
Regenerative medicine has greatly progressed, but tendon regeneration mechanisms and robust in vitro tendon differentiation protocols remain to be elucidated. Recently, tendon explant co-culture (CO) has been proposed as an in vitro model to recapitulate the microenvironment driving tendon development and regeneration. Here, we explored standardised protocols for production and storage of bioactive tendon-derived secretomes with an evaluation of their teno-inductive effects on ovine amniotic epithelial cells (AECs). Teno-inductive soluble factors were released in culture-conditioned media (CM) only in response to active communication between tendon explants and stem cells (CMCO). Unsuccessful tenogenic differentiation in AECs was noted when exposed to CM collected from tendon explants (CMFT) only, whereas CMCO upregulated SCXB, COL I and TNMD transcripts, in AECs, alongside stimulation of the development of mature 3D tendon-like structures enriched in TNMD and COL I extracellular matrix proteins. Furthermore, although the tenogenic effect on AECs was partially inhibited by freezing CMCO, this effect could be recovered by application of an in vivo-like physiological oxygen (2% O2) environment during AECs tenogenesis. Therefore, CMCO can be considered as a waste tissue product with the potential to be used for the development of regenerative bio-inspired devices to innovate tissue engineering application to tendon differentiation and healing.